1991
DOI: 10.1172/jci115237
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Na/H antiporter activity in rabbit renal brush border membrane vesicles.

Abstract: The development of the Na/H antiporter was studied in renal brush border membrane vesicles (BBMV) from fetal and adult rabbits using isotopic and fluorescent techniques. The kinetics of the antiporter studied by 'Na' uptake revealed that the V.,. was only 25% of that in the adult; however, the K.'s for Na'were not significantly different. These data were confirmed by a fluorescent assay using the pH-sensitive probe, acridine orange: the V.. was significantly lower in the fetal BBMV. Conductive Na' movement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…There is also evidence that the developmental increase in proximal tubule Na ϩ /H ϩ antiporter activity is responsible for inducing the postnatal increase in basolateral Na ϩ -K ϩ -ATPase activity (14). We have previously demonstrated that there is a maturational increase in rabbit PCT Na ϩ /H ϩ antiporter activity (2,15), and others have confirmed this using rabbit BBMV (16). However, Na ϩ /H ϩ antiporter activity in rat renal BBMV was found to be higher in neonates than in adults (17), raising the possibility that our findings (2,15) and those of Beck et al (16) may be peculiar to the rabbit.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…There is also evidence that the developmental increase in proximal tubule Na ϩ /H ϩ antiporter activity is responsible for inducing the postnatal increase in basolateral Na ϩ -K ϩ -ATPase activity (14). We have previously demonstrated that there is a maturational increase in rabbit PCT Na ϩ /H ϩ antiporter activity (2,15), and others have confirmed this using rabbit BBMV (16). However, Na ϩ /H ϩ antiporter activity in rat renal BBMV was found to be higher in neonates than in adults (17), raising the possibility that our findings (2,15) and those of Beck et al (16) may be peculiar to the rabbit.…”
mentioning
confidence: 56%
“…4-Acetamido-4Ј-isothiocyano-stilbene-2,2Ј disulfonic acid (SITS, 1 mM) was present in the bathing solution to inhibit the sodium bicarbonate cotransporter, a major regulator of intracellular pH i in PCTs (15,18). The bathing solution had a bicarbonate concentration of 5 mM and a pH of 6.6 to compensate for the cell alkalinization caused by the addition of bath SITS (16,18). The bathing solution was exchanged at a rate of 5 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal proximal tubules have a lower rate of glucose (3,4) and proline (38) transport than adult proximal tubules. Although prenatal administration of g1ucocorticoids has been shown to accelerate the maturation of the renal apical Na"/H+ antiporter (2, 7), basolateral Na(HC0 3 h symporter (2), and basolateral Na+-K+-ATPase activity (I, [8][9][10], it had no effect on glucose transport (2,7). In the present study, we measured Na-dependent glucose and proline transport as a control to determine whether there was a nonspecific inhibition in 88M transport in dexamethasone-treated neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The cortex was isolated and homogenized with a Teflon-glass Potter Eljevhem homogenizer. 88M vesicles were then isolated by differential centrifugation and magnesium precipitation as previously described (4,7,20,21). The final 88M vesicle fraction was resuspended in the above buffer at an approximate concentration of 10 mg 88M protein/ml, for equilibrium binding studies.…”
Section: Bbm Vesicle Isolationmentioning
confidence: 99%
See 1 more Smart Citation